Pengaruh Biaya Promosi Terhadap Penjualan pada PT Bukit Uluwatu Villa Tbk - Brigitta Elgiva; Junita Vany; Kharis Aldo Kilapong; Daniel Jehovah; Dyah Cahyasari (Yayasan Literasi Sains Indonesia, 2023)
This research aims to assess the influence of promotional expenses on sales. The population focus of this study is the quarterly financial reports from PT Bukit Uluwatu Villa Tbk. The analyzed data includes information from the company's financial statements and profit and loss reports. Sample selection was carried out using a non-random (non-probability sampling) approach, applying purposive sampling methods. The sample consists of 35 quarterly financial reports covering the period from 2015 to 2023. The analysis process employed simple regression analysis using the SPSS statistical software. The promotional expense variable is measured by the total promotional expenses, while the sales variable is measured by total sales. This research provides valuable insights for PT Bukit Uluwatu Villa Tbk to optimize their marketing strategies, considering the importance of managing promotional expenses to enhance future sales outcomes. The analysis results indicate a significant influence of the promotional expense variable on sales at PT Bukit Uluwatu Villa Tbk. In other words, promotional expenses play a crucial role in influencing the company's sales performance.